In the Disruption 4.0 Era, What Should the Government and the People Do? - Paramita Khodijah; Lubna Salsabila; Timbul Dompak; Karol Teovani Lodan (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
The purpose of this study is to explore how public discontent with government policies is addressed. This is a descriptive qualitative study that describes how the collective treatment of perspectives carried out in policies is in line with current social conditions. The goal is to avoid misunderstandings between municipal and federal governments. The following step is to discover the truth. Individuals involved in policy implementation must be able to explain their policies to members of the public. Furthermore, the policy should be founded on execution integrity so that the recipient understands the action. Policy knowledge may conflict with what is happening on the ground. To increase public trust in the government, the implementation of handling public opinion in the form of documents, pictures, and related policies by the government itself must be done openly, honestly, and responsibly. Environmental conditions and inter-organizational relationships may have an impact. Characteristics, organizational resources for program implementation, and the government's ability to overcome them which is guided by general guidelines for public service implementation: openness, accountability, status, participation, and equality.